Learning Problems during The Covid 19 Pandemic at SDN 65 Lebong - Joko Prayudha.S (Tarbawi, 2020)
This study aims to identify and investigate problems that occur in learning during the Covid 19 pandemic at SD Negeri 65 Lebong. The method used in this research is qualitative using a descriptive approach. In collecting data using questionnaires that are distributed via Google form and interviews which are carried out using Whatsapp. The population used in this study were all teachers in SD Negeri 65 Lebong, but for the sample using random sampling. The results showed that there were several problems faced by teachers including learning media, internet connection, spending quotas, lack of understanding of learning technology, low student motivation. Ongoing problems will be an obstacle for students to achieve learning achievement.